(untitled) (Qualitative Research Journal for Social Studies, 2025)
This study examines the principle of prior warning (inzar wa i’lam) before warfare in Islamic jurisprudence, demonstrating that it is not merely an ethical recommendation but a legal obligation, especially toward those who have not received the invitation to Islam. Classical jurists such as Abu Hanifa, Malik, al-Shafi’i, and Ahmad ibn Hanbal established conditions distinguishing between those to whom the message has or has not reached, making invitation mandatory in the latter case. The rationale, as detailed by jurists like al-Sarakhsi and Ibn Abidin, lies in offering adversaries a chance to avoid bloodshed by accepting Islam or paying jizya. Historical precedents—such as Umar ibn al-Khattab’s letters instructing threefold invitations and the tribunal under Umar ibn Abd al-Aziz correcting the Samarkand conquest—illustrate its legal weight in Islamic governance. International law similarly recognized advance declaration of war as a legal requirement, notably in the 1907 Hague Convention (III), but 20th-century treaties such as the 1928 Kellogg–Briand Pact and the 1945 UN Charter largely abolished formal declarations of war in favor of outlawing force, except for self-defense and Security Council authorization. Despite this evolution, both Islamic and international traditions reveal a shared commitment to limiting warfare’s devastation, protecting civilians, and prioritizing peaceful settlement. The principle of warning before hostilities remains a key legal and moral measure for reducing harm and fostering accountability in war.